Ethics and human rights in the hospital service by COVID-19 - Palomeque Cruz, Leticia (Horizonte Sanitario, 2023)
Objective: To analyze the experiences of international organizations and the Government of Mexico in establishing recommendations to protect the human rights of users of hospital services due to COVID-19, taking into account medical ethics. Materials and methods: This research focused on a qualitative approach, where experiences, perspectives, and approaches to ethics and human rights during the COVID-19 pandemic were analyzed. With this, books, scientific articles, reports and official documents of the organizations and dependencies involved were studied. Results: In the coronavirus pandemic, health systems were forced to seek support from civil society to counter its negative effects on the economy and the protection of human rights. However, today, the task of the health sector continues, since cases of COVID-19 continue to arise, in addition, there are patients who still have sequelae and who must be treated without exclusion. So that timely, acceptable and affordable access to health services with sufficient quality continues to be privileged. Conclusions: The COVID-19 pandemic modified the enjoyment of human rights, including the right to health, for which reason medical work was modified based on the recommendations of international organizations and governments of the three levels. In the care of the health emergency, it was essential to protect human integrity; act with respect, solidarity, empathy and reciprocity; and understanding that everyone should be cared for without discrimination, that is, with inclusion and considering the existence of vulnerable groups, basing care on medical ethics and values. Keywords: Human rights; COVID-19; Ethics; Public politics.